Analisis Resepsi Remaja Perempuan terhadap Gaya Hidup Berbelanja Fashion Melalui Tayangan Video ‘Belanja Gak Aturan’ dalam Akun Tiktok @handmadeshoesby - Purnamasari, Nurjihan Pricillia; Tutiasri, Ririn Puspita (representamen, 2021)
This research was conducted to analyze the reception of teenage girls in the case of shopping lifestyle which has been shown through the video entitled "Shopping without any limit" on the @Handmadeshoesby tiktok account. In this video, there is a woman who went shopping for fashion products without any shopping list and she took a large quantity of fashion product without any consideration or trying out the product first. This has attracted researcher to find out how teenage girls interpret the messages in the video. This study used a qualitative research method with a reception analysis study. The number of informants was 10 people. The research used interviews and observation as a data collection techniques. This research uses Stuart Hall's encoding-decoding theory in which the message creator made messages with certain meanings that are expected to be accepted by the audience. But the audience can also interpret messages according to their own experiences. The results showed that there were differences in the reception between one informant and another. The reception of young women to the video “Shopping without any limit” that was displayed @Handmadeshoesby tiktok account has different interpretations. The aspects presented in the video were not fully approved by the informants. These interpretations comes from knowledge and experiences gained from everyday life.Keywords : Lifestyle, tiktok, reception analysis